“Respuesta de la fertilización de NPK en el cultivo del tomate (lycopersicum esculentum), var. “Rio Grande”, en función al rendimiento en la provincia de Lamas – San Martín” - Gonzales Becerra, Juan Ali (2016)
The present research work entitled "response of fertilization in the cultivation of tomato (Lycopersicon esculentum), in the Rio Grande variety depending on the performance of sows in the province of Lamas, San Martin - Peru", had the purpose of evaluating the effect of three doses of NPK in tomato crop yield, as well as determine the dosage of NPK, enabling the best development of the plant and the highest yield of the crop. We used a quantitative research, applying a design of blocks totally at random (DBCA), with 4 treatments and an absolute control with 4 replications per treatment, the treatments were: witness T 0: without NPK, T1: NPK: 200-50-180, T2: NPK: 240-100-220, T3: NPK: 280-150-260. The variables evaluated were: plant height, number of fruits per plant, weight of fruit, the fruit diameter and length of the fruit, kg.ha-1 performance and economic analysis. The most relevant conclusions were: greater plant height was achieved with T 2 and T 3 treatments with 117 cm and 108, 1 cm. Treatment T2 was awarded the largest diameter of the fruit with 4,91 cm, length of the fruit reached the highest average with 8,07 cm and similarly yield obtained the T2 was 55 817,0 kg.ha-1, followed by the T3 with 31 841,0 kg.ha-1 being the treatments that best answers presented. Treatments with doses of NPK: 200 - 50-180 (T1), retumed values C/B greater than 1, so obtained gains reflected in net profit. Being NPK treatment T 2: 240 - 100 - 220, which had the highest B/C with 2,49 and a net profit of S /. 16 695,90 per hectare, followed by NPK treatments T1: 200 - 50 - 180 and T3 NPK: 280 - 150-260, who obtained values B/C of 1,64 and 1,35 with net profit of S /. 5 850,50 and S l. 4 128,10 respectively. The T0 (control) treatment reported values of B/C of 0,98 with negative net profit of S l. -126.00 Respectively. Keywords: NPK, variety, Rio Grande, dosage, application, blocks, performance, cost benefit.